The Problematic Institutional Context of Greek Football and the Role of FIFA and UEFA - Pouliopoulos Theofilos; Georgiadis Konstantinos (Sciendo, 2022)
Greek football is on the periphery of European football and it frequently faces scandals and corruption issues. Also, there appears to be a correlation between the wider social and political context and football. Additionally, FIFA and UEFA arguably have contributed to the fate of Greek football. For example, in the past when the Greek government tried to intervene in football, FIFA prevented them several times with the threat of a ban. During the previous years, FIFA and UEFA decided to cooperate with the Greek government and play a more active role in Greek football. However, little has changed in the governance of Greek football. This study has examined the context, critical incidents and the role of actors in Greek football. By using the Institutional Theory approach, our analysis indicates that the institutional context is highly problematic, as the big clubs dominate the institutional mechanisms of football. Corruption appears to be deeply embedded in the structures and operations of football, while the Hellenic Football Federation is controlled by the big clubs. In parallel, there is no plan for the overall development of football, from the grassroots to the elite level. The study concludes with a recommendation for the reformation of Greek football.